OWE-024 The natural history of terminal ileal resection in crohn's disease. (8th June 2018) - Segal, Jonathan; Askari, Alan; Worley, Guy; Clark, Susan; Hart, Ailsa; Faiz, Omar
Abstract : Introduction: CD can affect any part of the GI tract but the terminal ileum (TI) is the most common. The incidence of CD in Europe ranges from 0.5 to 10.6 cases per 1 00 000 person-years. The risk of surgery based on all population-based studies, at 1, 5, and 10 years after diagnosis of CD is 16.3% (95% confidence interval [CI], 11.4%–23.2%), 33.3% (95% CI, 26.3%–42.1%), and 46.6% (95% CI, 37.7%–57.7%), respectively. The risk of reoperation following a TI resection has been reported as 70% at 20 years based on a population of 1379 patients. A recent study comparing laparoscopic ileal resection versus infliximab found that laparoscopic ileocaecal resection results in similar quality-of-life scores and is not associated with more serious adverse events. The long-term outcomes of those undergoing ileal resection has yet to be studied and may help identify risk factors for those that may require further operations. Methods: The Hospital Episodes Statistics dataset was used to identify all patients admitted to hospitals in England from 1997–2012. Time trends and multivariate logistic regression analysis was undertaken to determine factors associated with repeated resection. Results: 1 55 236 patients were identified as having a diagnosis of CD with a median follow-up was 92 months (IQR 43–143). Of these, 18.8% (29, 257) underwent TI resection. Amongst this sub-group, 11.0% (n=3, 101/29, 257) required more than one resection. The total number of procedures performed was 32, 889, of which 56.6% (n=18, 622/32, 889) were right hemicolectomy/ileo-caecal resection. The median time between resections was 41 months (IQR 15–74 months). There was no significant change in the number of procedures performed each year (p=0.693). Of the total population, 7.8% (n=12, 173/155, 236) had Infliximab therapy. At multivariate analyses, patients on Infliximab were more likely to undergo multiple resections (OR 1.47, 95% CI 1.41–1.53, p<0.001), possibly indicating severity of disease. Elderly patients (80+years) were less likely to undergo surgical resection (OR 0.13, 95% CI 0.12–0.15, p<0.001). There was no differences in gender. Conclusion: Nearly one in five patients will require surgical intervention over a 15 year period for CD, of those undergoing TI resection only 11% of these will require further surgery. This is the largest population based study reporting the requirement for further surgery following TI resection and suggests that the reoperation rate is far lower than previously reported. The number of procedures performed has largely remained the same overtime suggesting that medical therapy has not altered the overall rates of further surgery following TI surgery in CD.